Global trends in poliomyelitis research over the past 20 years: A bibliometric analysis - Qi Liu; Ze Liu; Biling Huang; Yuanyuan Teng; Mingliu Li; Shuqin Peng; Hongbin Guo; Min Wang; Jieyu Liang; Yi Zhang (Taylor & Francis Group, 2023)
Poliomyelitis is an acute infectious disease caused by poliovirus. This bibliometric analysis aims to examine the status of poliomyelitis research in the past 20 years. Information regarding polio research was obtained from the Web of Science Core Collection database. CiteSpace, VOSviewer, and Excel were used to perform visual and bibliometric analysis with respect to countries/regions, institutions, authors, journals and keywords. A total of 5,335 publications on poliomyelitis were published from 2002 to 2021. The USA was the county with the majority of publications. Additionally, the most productive institution was the Centers for Disease Control and Prevention. Sutter, RW produced the most papers and had the most co-citations. Vaccine was the journal with the most polio-related publications and citations. The most common keywords were mainly about polio immunology research ("polio," "immunization," "children," "eradication" and "vaccine"). Our study is helpful for identifying research hotspots and providing direction for future research on poliomyelitis.